2020
DOI: 10.22271/ortho.2020.v6.i1f.1885
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and clinical outcome of conservative management of thoracolumbar spinal tuberculosis in adults

Abstract: Introduction: Potts disease continues to be a major health problem in developing and underdeveloped countries. Patients who exhibit both kyphotic deformity and minimal neurological impairment and can be managed conservatively which may be achieved by chemotherapy alone, surgical indications in these patients are specific and few. Since the last decade there is paucity of literature regarding the conservative management of thoraco-lumbar spinal tuberculosis with increasing trend toward more and more surgical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The radiographic highlights of osteoarticular tuberculosis are vague [2,3,10] . Radiographic findings are normally noted 2-5 months after the start of illness and just a joint effusion might be evident in the beginning phase [11,12] . The typical radiographic presentation of tuberculous arthritis is portrayed by juxta-articular osteoporosis, peripheral osseous erosions and steady decrease of joint space, known as the Phemister triad [11,12] , is not a common entity in calcaneum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The radiographic highlights of osteoarticular tuberculosis are vague [2,3,10] . Radiographic findings are normally noted 2-5 months after the start of illness and just a joint effusion might be evident in the beginning phase [11,12] . The typical radiographic presentation of tuberculous arthritis is portrayed by juxta-articular osteoporosis, peripheral osseous erosions and steady decrease of joint space, known as the Phemister triad [11,12] , is not a common entity in calcaneum.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic findings are normally noted 2-5 months after the start of illness and just a joint effusion might be evident in the beginning phase [11,12] . The typical radiographic presentation of tuberculous arthritis is portrayed by juxta-articular osteoporosis, peripheral osseous erosions and steady decrease of joint space, known as the Phemister triad [11,12] , is not a common entity in calcaneum. Lytic territories of destruction and minor erosions are regularly observed along the articular edges in weight-bearing articulations such as the hip, knee and ankle [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the Phemister triad (peripheral bony erosion, decreased joint space and juxta-articular osteoporosis), is not commonly seen in calcaneal TB. [10,26] Dhillon et al [7] study on foot TB showed that out of 92 cases, the cystic form was seen in 24 cases. In contrast, a study by Mittal et al [15] showed the presence of the cystic form in only 15 cases out of 44.…”
Section: -Year-malementioning
confidence: 99%